Assessment of Potentials of Historic Sites in Boosting Tourism Development: A Case Study of Arondizogu, lmo State - Iwuagwu, Nonso; Kukoyi, Ibrahim A. (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Cultural heritage is a main issue for the identity of different nations. In the 21st century, the increasing urbanization of the world coupled with global issues of environmental degradation, economic restructuring and social exclusion, demand that we take a deeper look of the future of cultural and heritage sites. Arondizogu community is made up of so many historic sites, however most of these cultural heritage sites are partially or completely deteriorated due to lack of proper planning, development and documentation, hence modernization theory of development was employed in the study. Cultural heritage and historic sites have lost their dynamism especially during the recent years necessitating the urgent need for development. As cultural heritage sites are considered as a part of a nation’s assets, Nigeria must reconsider her way of planning, managing, developing and conserving these sites. Therefore this paper attempts to explore the possibility of using the potentials of cultural heritage sites as a resource to boost tourism development thereby increasing our national income through good management. Findings were made through interviews and personal observations, the study was concluded by recommending proposed guideline planning methodology for government, NGOs, and conservation specialists etc, which will help them in establishing a sustainable cultural heritage sites.